New drugs in psychiatry - cariprazine, lurasidone, esketamine - Pożarowska Kinga (Sciendo, 2021)
Introduction: Invariably, the search for an “ideal drug” in psychiatry has been going for years, one that is safe and effective, prevents relapse and shows the least possible side effects.